Degradation of per- and polyfluoroalkyl substances in landfill leachate by a thin-water-film nonthermal plasma reactor. (15th April 2023) - Eeso, Karam; Gallan, Rachel; Goukeh, Mojtaba Nouri; Tate, Kerry; Raja, Radha Krishna Bulusu; Popovic, Zeljka; Abichou, Tarek; Chen, Huan; Locke, Bruce R.; Tang, Youneng
Graphical abstract: Abstract: Per- and polyfluoroalkyl substances (PFAS) are present in landfill leachate, posing potential challenges to leachate disposal and treatment. This work represents the first study of a thin-water-film nonthermal plasma reactor for PFAS degradation in landfill leachate. Of the 30 PFAS measured in three raw leachates, 21 were above the detection limits. The removal percentage depended on the category of PFAS. For example, perfluorooctanoic acid PFOA (C8) had the highest removal percentage (77% as an average of the three leachates) of the perfluoroalkyl carboxylic acids (PFCAs) category. The removal percentage decreased when the carbon number increased from 8 to 11 and decreased from 8 to 4. The effects of various landfill leachate components, including sodium chloride, acetate, humic acids, pH, and surfactants, had no or minor impacts (<30%) on PFOA mineralization in synthetic samples. This might be explained by the plasma-generation and PFAS-degradation mainly occurring at the gas/liquid interface. Shorter-chain PFCAs were produced as intermediates of PFOA degradation, and shorter-chain PFCAs and perfluorosulfonic acids (PFSAs) were produced as intermediates of perfluorooctanesulfonic acid (PFOS). The concentrations of the intermediates decreased with decreasing carbon number, suggesting a stepwise removal of difluoromethylene (CF2 ) in the degradation pathway. Potential PFAS species in the raw and treated leachates were identified at the molecular level through non-targeted Fourier-transform ion cyclotron resonance mass spectrometry (FT-ICR MS). The intermediates did not show accurate toxicity per Microtox bioassay.